ANALYSIS OF ROAD DAMAGE USING THE PAVEMENT CONDITION INDEX METHOD ON THE LAMONGAN CITY – MOJOKERTO BORDER ROAD SECTION - Mashudi, Anang; Muhammadun, Haris; Marleno, Risma (Transpublika Publisher, 2024)
Road as an important facility for the community to achieve a desired goal both mobilizing goods and services. On the Lamongan City – Mojokerto border road section STA 20+000 - 26+000 based on the field has experienced a decrease in road services that are not stable / comfortable with a lot of damage to the road. This study aims to determine how much the pavement performance index is with the Pavement Condition Index (PCI) method, determine the handling of road maintenance and the cost of handling road maintenance based on the two methods. From the research results, the value of the pavement performance index based on the Pavement Condition Index (PCI) method is 72.1%, this is in the good category and includes a periodic maintenance handling program, the cost of handling road maintenance with the Pavement Condition Index (PCI) method is Rp. 15,614,599,505.96.